Wirtschaftswissenschaften: zu wenig Pluralität der Methoden und Forschungsrichtungen? - Johannes Becker; Sebastian Dullien; Rüdiger Bachmann; Silja Graupe; Arne Heise (Wirtschaftsdienst, 2017)
Der sogenannten Mainstream-Ökonomie wird vorgeworfen, ihren Methoden liege ein zu einfaches Menschenbild zugrunde, sie sei geschichtsvergessen, und sie habe nicht rechtzeitig vor der Finanzkrise gewarnt. Wirtschaftswissenschaftler verschiedener Richtungen debattieren hier darüber, was Pluralität oder Mainstream bedeuten, ob der Mainstream die Lehre beherrscht und inwieweit Pluralität in der Forschung zugelassen wird. Nicht zuletzt wird der Frage nachgegangen, welche Auswirkungen eine Mainstream-Ökonomie auf die Politikempfehlungen hat. – – The authors discuss the merits of including pluralist methods, theories and paradigms into the traditionally mainstream. They also evaluate the progress made by German faculties in this regard. The pluralism debate is in itself plural. There are numerous international and Germany specifi c dimensions and associated critiques of mainstream economics. Different approaches to economic policy must be organised in a manner which guarantees theoretical and paradigmatic pluralism - on which economic policy proposals ought to be based. Another view focuses on the educational effect and states that the mental frames of economics students are subject to manipulation; the foundation of their thinking is narrowed and recontextualised in an emotionally and politically highly charged semantic environment.
Keywords: A11; A12; B41; B50; N01; 330